Soft-templating synthesis of mesoporous magnetic CuFe2O4 thin films with ordered 3D honeycomb structure and partially inverted nanocrystalline spinel domains - Reitz, Christian; Suchomski, Christian; Haetge, Jan; Leichtweiss, Thomas; Jaglicic, Zvonko; Djerdj, Igor; Brezesinski, Torsten; Justus Liebig University Giessen (My University, 2012)
Combining sol gel chemistry with polymer templating strategies enables production of CuFe2O4 thin films with both an ordered cubic network of 17 nm diameter pores and tunable spinel domain sizes. These nanocrystalline materials contain only minor structural defects with ? = 0.85 ± 0.02 and exhibit multiple functionalities, including superparamagnetic behavior (TB 310 K) and redox- and photoactivity.
Keywords: ddc:540